ERADICATING POVERTY THROUGH EDUCATION: THE KEY ROLE OF SKILLS DEVELOPMENT - Hayitmurodova Gulinur Zafarovna (Bright Mind Publishing, 2025)
This article sheds light on the role of education in eradicating poverty. It gives information about how poor and underdeveloped countries can dramatically reduce the level of poverty by improving their education system and encouraging children to go to schools instead of hard physical labour. There are many, various and interconnected causes of poverty, and we can't use a magic formula to eradicate it. But we can consider education as a reducing risk element of high poverty, which may prevent the occurrence of another generation, much poorer
Keywords: Education, poverty, income, economy, modern workforce, earnings, innovation, creativity, children.